Goat medicine - Smith, Mary C.; Sherman, David M. (Wiley-Blackwell, 2009)
Fully revised and expanded, Goat Medicine, Second Edition includes discussions on new diseases ranging from bovine spongiform encephalopathy to floppy kid disease as well as major updates on important diseases such as scrapie, mycoplasmosis, paratuberculosis, and urolithiasis